Activation of μ-opioid receptors inhibits calcium-currents in the vestibular afferent neurons of the rat through a cAMP dependent mechanism - Seseña, Emmanuel; Vega, Rosario; Soto, Enrique (Frontiers in Cellular Neuroscience, 2014)
Opioid receptors are expressed in the vestibular endorgans (afferent neurons and hair cells) and are activated by the efferent system, which modulates the discharge of action potentials in the vestibular afferent neurons (VANs). In mammals, the VANs mainly express the µ opioid-receptor, but the function of the opioid receptor activation and the cellular mechanisms by which they exert their actions in these neurons are poorly studied. To determine the actions of the µ opioid receptor (MOR) and the cell signaling mechanisms in the VANs, we made perforated patch-clamp recordings of VANs that were obtained from postnatal days 7 to 10 (P7-10) rats and then maintained in primary culture. The MOR agonist [D-Ala2, N-Me-Phe4, Gly5-ol]-enkephalin (DAMGO) inhibited the total voltage-gated outward current; this effect was prevented by the perfusion of a Ca2+-free extracellular solution. We then studied the voltage-gated calcium current (Ica) and found that DAMGO Met-enkephalin or endomorphine-1 inhibited the ICa in a dose-response fashion. The effects of DAMGO were prevented by the MOR antagonist (CTAP) or by the pertussis toxin (PTX). The use of specific calcium channel blockers showed that MOR activation inhibited the T-, L- and N-type ICa. The use of various enzyme activators and inhibitors and of cAMP analogs allowed us to demonstrate that the MOR acts through a cAMP dependent signaling mechanism. In the current clamp experiments, MOR activation increased the duration and decreased the amplitude of the action potentials and modulated the discharge to the current injection. Pre-incubation with PTX occluded all MOR activation effects observed in the current clamp experiments. We conclude that MOR activation inhibits the T-, L- and N-type ICa through the activation of a Gi/o protein that involves a decrease in AC-cAMP-PKA activity. The modulation of ICa may have an impact on the synaptic integration, excitability and neurotransmitter release from the VANs.